PARKEY: Ticket-less parking system using license plate recognition approach - Kamaruzaman M.A.M.B.; Nasir N.R.M. (IOP Publishing Ltd, 2023)
Benchmarking; Image recognition; License plates (automobile); Elicitation techniques; Existing systems; Image recognition technology; License plate recognition; Payment systems; Potential users; Virtual Tickets; WEB application; Optical character recognition